Parameter testing and application of the 3PG model for Eucalyptus grandis x urophylla on the Zululand coastal plain, South Africa - Gakenou, Oluwaseun (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc) -- Stellenbosch University, 2021.